Does Hot Money Impact Stock And Exchange Rate Markets On China? - Lee , Yen Hsien; Huang , Ya Ling; Chen , Tsu Hu (Asian Academy of Management (AAM), 2017)
d the returns and volatility spillover between the stock and exchange rate market in China by using the monthly data covering the period from July 2005 to June 2013. This paper also uses the quantile approach to determine whether the hot money inﬂuences the stock and exchange rate markets. The results frst reveal the long-run equilibrium relationship that is exhibited between the stock and exchange rate market. Second, hot money has an impact on the stock market but has no eﬀect on the exchange rate market, according to the VECMBEKK model. Third, regarding the volatility spillover eﬀects on the stock and exchange rate markets, there is a spillover eﬀect on the Shanghai stock and exchange rate markets. Hot money has an impact on the stock and exchange rate markets. Finally, we apply the quantile regression to determine the impact of hot money on low quantiles of the exchange rate and high quantiles of the Shanghai and Shenzhen stock market